Interesting South African Scale lnsects (Hemiptera: Coccoidea) (Bollettino di zoologia agraria e bachicoltura, 2024)
The South African scale insect fauna comprise a number of species that are very interesting from historical taxonomic or biologicalperspectives. Thus it has a species described by Linnaeus in 1763, species with peculiar characters that confuse taxonomists and five gall-inducers from five different scale insect families. It also has two species in the Diaspididae where the female lacks the typical "armour" of the family when it is found living in ant galleries on plants.
Keywords: scale insects; Coccoidea; insect galls